THE MEANING OF ‘KAPUHUNAN’ TRADITION IN BANJARMASIN: AN EXPLORATION OF VIRTUES FROM A POSITIVE PSYCHOLOGY PERSPECTIVE: English - Anshary, Muhammad Ridha; Nurhayati, Siti Rohmah; Herwin, Herwin; Kasyfillah, Muhammad Haidarsyah (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2025)
The Kapuhunan tradition is a tradition of sharing food and sincerely accepting the gifts of others, which includes moral messages and virtues from a positive psychology perspective. This study aims to explore and describe the Banjar people's understanding of the kapuhunan tradition, identify and analyze the virtues contained in the kapuhunan tradition, and explain how these virtues are implemented in the lives of the Banjar people. Using a phenomenological qualitative approach, data was collected through in-depth interviews with several Banjar students from southern Kalimantan living in jogja dormitory with a sample size of 3-5 participants and observations. The results showed that the kapuhunan tradition contains virtues such as kindness, respect for others, and social solidarity, which are reflected in the practice of sharing food and receiving gifts from others. This research contributes to the development of positive psychology that is more sensitive to the Indonesian cultural context, and serves as a foundation for the preservation and revitalization of positive values in Banjar culture. As such, it provides new insights into the potential of virtue values in the local traditions of Indonesian society.